2016
DOI: 10.18632/oncotarget.10099
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of distant metastasis in Chinese women according to breast cancer subtypes

Abstract: To access possible relationships between breast cancer subtypes (BCS) and patterns of distant metastasis in advanced breast cancer. Breast cancer patients with distant metastasis at two academic centers from 2000-2015 were retrospectively reviewed. The breast cancer was classified into four subtypes: hormone receptor (HR) +/ human epidermal growth factor receptor 2 (HER2) − (i.e., estrogen receptor [ER] + and/or progesterone receptor [PR] +, HER2−); HR+/HER2+ (ER+ and/or PR+, HER2+), HR−/HER2+ (ER− and PR−, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
7
15
0
3
Order By: Relevance
“…We found that the patients with the HR−/HER2− subtype were more likely to develop BM in our previous study 24. In this study, significant differences in the number of BM were observed across the different BCSs.…”
Section: Discussionsupporting
confidence: 50%
“…We found that the patients with the HR−/HER2− subtype were more likely to develop BM in our previous study 24. In this study, significant differences in the number of BM were observed across the different BCSs.…”
Section: Discussionsupporting
confidence: 50%
“…Importantly, this study revealed the subtype-based differential susceptibility to distant metastasis in the contemporary era of breast cancer treatment. Several previous reports have explored the subtype-related preferential sites of distant metastasis [16,[21][22][23][24][25][26]. However, their results were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…and hormone receptor-negative/HER2(?) tumors were more prone to abdominal or pelvic metastasis, compared to patients with a hormone receptor-positive/HER2(-) tumor [adjusted odds ratio (aOR) 1.665, 95% CI 1.096-2.530; aOR 1.971, 95% CI 1.244-3.124, respectively] [26]. An early bioinformatics study found an association of Wnt signaling and focal adhesion factors with molecular subtypes and relapsed organs [27].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the absence of distant metastasis in colorectal cancer, surgery with curative intent is a common treatment modality, and adjuvant therapy is rarely essential if there is no evidence of lymphatic involvement . Past studies have examined patterns of metastasis and provide evidence that there are differences in the frequency, pattern, and site of distant metastasis for various primary tumors . In a comprehensive analysis of 16 major tumor sites, Budczies et al.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the absence of distant metastasis in colorectal cancer, surgery with curative intent is a common treatment modality, and adjuvant therapy is rarely essential if there is no evidence of lymphatic involvement [10]. Past studies have examined patterns of metastasis and provide evidence that there are differences in the frequency, pattern, and site of distant metastasis for various primary tumors [8,[11][12][13][14]. In a comprehensive analysis of 16 major tumor sites, Budczies et al observed major differences in the frequency of metastasis across sites, with melanoma and breast cancers having the highest mean number of metastasis per case (5.9 and 5.2, respectively), and liver cancer with the lowest mean number of metastasis (2.3) [8].…”
mentioning
confidence: 99%